Elevated atmospheric CO2 causes seasonal changes in carbonyl emissions from Quercus ilex (New Phytologist, 2002)
* • The effect of elevated atmospheric CO2 on the carbonyl emissions of leaves from two Mediterranean oak species (Quercus ilex and Q. pubescens) was analyzed under field conditions. * • Physiological and meteorological parameters were determined in parallel with measurements of carbonyl emissions. Gas exchange was quantified in dynamic cuvettes combined with an infrared gas analyzer. * • Acetaldehyde and acetone emissions from leaves of Q. ilex were enhanced by elevated CO2 in the autumn (from 14–40 nmol m−2 min−1 and from 2–8 nmol m−2 min−1, respectively), but not in the summer. No significant effects were found for leaves of Q. pubescens. The effects of CO2 on Q. ilex were mainly a result of decreased emissions by control trees under ambient CO2 concentrations in the autumn; emissions from trees exposed to elevated CO2 remained at a high level. * • Elevated atmospheric CO2 causes autumnal changes in carbonyl emissions from Quercus ilex. These effects suggest that the production of acetaldehyde and acetone depend on developmental factors. It is not yet clear whether the altered carbonyl emissions are a unique feature of Q. ilex.